The Students' Perception towards Madurese Traditional Culinary-Based Teaching Materials of English for Higher Education - Badrut Tamam; Slamet Setiawan; Syafi’ul Anam; Jihat Nurrahman (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2020)
This present study aimed at describing the students' perception towards Madurese traditional culinary based teaching materials of English in higher education level in Sumenep Madura. This is a survey research which is triangulated with three instruments used in collecting data namely: observation field notes, questionnaire, and interview. The result showed that the English learning material which was equipped with Madurese traditional culinary got a positive perception and higher appreciation from the students in terms of materials' attraction, materials' usefulness, materials' difficulty, materials' variety, materials' authenticity, and proportion of the four language skills. Further, the students can happily and enthusiastically join the English language learning. They said that they could recognize the madurese culinary deeper than before. In addition, traditional culinary can be used as the identity that can promote the region to overseas. Moreover, in terms of English language teaching, the traditional culinary can be used as valuable materials which can help to promote and maintain local wisdom.